2017
DOI: 10.1111/pala.12319
|View full text |Cite
|
Sign up to set email alerts
|

Eocene Pachynolophinae (Perissodactyla, Palaeotheriidae) from China, and their palaeobiogeographical implications

Abstract: The Eocene perissodactyl family Palaeotheriidae has traditionally been considered to be a nearly endemic European group within Equoidea, but a few palaeotheres have been reported from Asia. Here, I reanalyse a maxilla containing M1-3 from the Lunan Basin, Yunnan Province, China. This element was initially assigned to a new tapiromorph species, Lophialetes yunnanensis, but is here placed in a new genus Lophiohippus within Pachynolophinae based mainly on the absence of mesostyles, the strongly oblique metalophs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…More recent study, however, suggested that ‘ P .’ hengyangensis resembles Danjiangia based on p3-m2 morphology 32 . Both Danjiangia and ‘ Propalaeotherium ’ sinense have striking similarities to Lambdotherium , a basal brontothere 43 . However, we suggest that the three specimens that Ting referred to ‘ P .’ hengyangensis probably represent at least two different groups of perissodactyls.…”
Section: Resultsmentioning
confidence: 99%
“…More recent study, however, suggested that ‘ P .’ hengyangensis resembles Danjiangia based on p3-m2 morphology 32 . Both Danjiangia and ‘ Propalaeotherium ’ sinense have striking similarities to Lambdotherium , a basal brontothere 43 . However, we suggest that the three specimens that Ting referred to ‘ P .’ hengyangensis probably represent at least two different groups of perissodactyls.…”
Section: Resultsmentioning
confidence: 99%
“…to MP20) Western Europe was isolated from Northern Europe by the North Sea and Northern Europe from Asia by the Turgaï Strait [ 16 , 18 , 112 , 139 – 141 ]. Regarding South Alpine-Carpathian Europe, it was mostly disconnected from the rest of Europe by the Perialpine and Paratethys seas—they may have been in connection at some point [ 142 , 143 ]—but connected to Asia [ 112 , 140 , 141 ]. Perissodactyl faunas in this part of Europe seem more similar to those found in Asia (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The Palaeotheriidae include both tetradactyl and tridactyl members (Agusti and Anton 2004;Franzen 2006Franzen , 2010bDanilo et al 2013), and as a result may be expected to demonstrate a high degree of morphological variation in the forelimb. The first descriptions of palaeotheres are those of the currently recognized Palaeotheriinae (Cuvier 1812), a monophyletic clade which includes the genera Palaeotherium and Plagiolophus (Danilo et al 2013;Remy 2015;Bai 2017). These two genera are both functionally tridactyl palaeothere clades; however, despite their close phylogenetic affinity, they demonstrate high morphological diversity within the forelimb (Figs 2, 5 and 6).…”
Section: Locomotor Diversity Within Palaeotheriinaementioning
confidence: 99%